China and transparency norm development in global extractives governance - Park, Hyeyoon, author; Betsill, Michele, advisor; Harris, Pete, committee member; Duffy, Robert, committee member; Malin, Stephanie, committee member (Colorado State University. Libraries, 2021)
Growing global demand for extractive resources, such as metals and minerals, particularly to produce low-carbon products, requires international society to develop effective global governance mechanisms to mitigate some of the environmentally and socially negative impacts of mining operations beyond national borders. Since early 2000, several transnational extractive governance initiatives (TEGI) have been established, and these initiatives commonly emphasize a transparency norm to cope with these new global challenges. At the same time, the influence of Chinese actors in global extractive sectors has been increasing along with China's rapid economic growth and rising natural resources demands. Notably, Chinese actors have started engaging in TEGIs and recently appear to take a more active role in global extractives governance. This dissertation examines whether China is a norm-taker or a norm-maker in transparency norm development processes of global extractives governance to understand this new phenomenon. In addition, this research seeks to answer under what conditions China is a norm-taker or a norm-maker and how power matters in transparency norm development. To date, there has been limited research on transnational extractives governance as an independent governance architecture within the system of global environmental governance. In addition, few International Relations (IR) and global governance scholars have examined China's normative role in global governance. In particular, there is a lack of understanding of China's normative role in "re-shaping" existing norms in global governance. This dissertation aims to fill the gaps in existing scholarship. By applying Acharya's (2018) norm-circulation model emphasizing two-way socialization processes, this dissertation find that Chinese actors take a global transparency norm, localize the norm based on China's local context, then universalize the localized transparency norm at the global level. Based on qualitative document analysis, semi-structured interviews, and process-tracing, this research includes a mapping exercise of 48 TEGIs and a case study of the Responsible Cobalt Initiative (RCI), a TEGI established by China in 2016 to improve the responsibility of upstream and downstream companies in the cobalt supply chain. The major findings show that Chinese actors act as both a norm-taker and a norm-maker. The mapping analysis shows that they more actively participate in TEGIs emphasizing a thin transparency norm that lacks the disclosure of information about decision-making processes to the public, the presence of an independent third-party auditor in monitoring processes, or the disclosure of the verification information to the public. The RCI case study reveals that the China Chamber of Commerce of Metals, Minerals and Chemical Importers and Exporters (CCCMC) acted as a local idea-shifter by localizing a global transparency norm and developing Chinese versions of transparency guidelines. CCCMC is trying to universalize their locally constituted norm at the transnational level through the RCI. China's role in facilitating a thin transparency norm could lead to green- or white-washing of extractive companies, given the less stringent characteristics of a thin transparency norm. I argue that CCCMC's efforts to universalize the localized Chinese version of transparency is based on their institutional and structural power supported by the Chinese government's sponsorship and its close ties with powerful business actors. These findings, notably, suggest that power facilitates or constrains agency of certain groups of actors seeking to play a norm-maker's role, particularly in a universalization process in Acharya's norm-circulation model. These findings resonate with realist constructivists' understanding of world politics, emphasizing both norms and power, beyond the fragmented paradigmatic debates in IR between realists and constructivists. Collectively, this dissertation contributes to the broader debates in IR and Global Environmental Politics about the rise of China in global governance, global norm development, and legitimacy and accountability of global environmental governance.